2019
DOI: 10.1111/irv.12686
|View full text |Cite
|
Sign up to set email alerts
|

Estimates for quality of life loss due to Respiratory Syncytial Virus

Abstract: BackgroundIn children aged <5 years in whom severe respiratory syncytial virus (RSV) episodes predominantly occur, there are currently no appropriate standardised instruments to estimate quality of life years (QALY) loss.ObjectivesWe estimated the age‐specific QALY loss due to RSV by developing a regression model which predicts the QALY loss without the use of standardised instruments.MethodsWe conducted a surveillance study which targeted confirmed RSV episodes in children aged <5 years (confirmed cases) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 19 publications
0
34
1
Order By: Relevance
“…They substantially contribute to morbidity and mortality worldwide [2]. Furthermore, RTI are associated with large societal impacts [3], including a high healtheconomic burden [4], caused by a high hospitalization rate among the very young, causing frequent parental absence from work [5]. Moreover, antimicrobial consumption is heavily driven by RTI [6] due to the clinical challenge of distinguishing between viral and bacterial etiologies and the lack of a reliable diagnostic reference standard [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…They substantially contribute to morbidity and mortality worldwide [2]. Furthermore, RTI are associated with large societal impacts [3], including a high healtheconomic burden [4], caused by a high hospitalization rate among the very young, causing frequent parental absence from work [5]. Moreover, antimicrobial consumption is heavily driven by RTI [6] due to the clinical challenge of distinguishing between viral and bacterial etiologies and the lack of a reliable diagnostic reference standard [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Comparing it to a baseline reported HRQoL at day 30 since onset of symptoms (Q30; baseline), we found that RSV was associated with a mean HRQoL loss in children and their parents of 38%, 32% and 9% during the first, second and third week after the diagnosis, respectively. These results are lower than the only published study estimating a model-estimated HRQoL loss of 0.54 (95% CI 0.14-0.95) in children under 5 years [24]. However, their estimates were not obtained directly, instead they used the responses from the older suspected cases.…”
Section: Discussionmentioning
confidence: 70%
“…The only publication identified determining QALY loss due to an RSV episode in individuals < 5 years old [ 24 ] is based on model predictions from older children (5–14 years old), instead of using an age-adapted questionnaire.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from England suggests that children under five with RSV face quality-adjusted life-year (QALY) losses due to the infection, although few studies explore the scale of this impact [18]. The evidence suggests a modest average impact on QALYs at the individual level in most cases due to the illness's short duration [18]. QALY losses also vary depending on whether healthcare is sought or not [18].…”
Section: Children With Rsv Experience a Loss Of Quality Of Life Due T...mentioning
confidence: 99%
“…The evidence suggests a modest average impact on QALYs at the individual level in most cases due to the illness's short duration [18]. QALY losses also vary depending on whether healthcare is sought or not [18].…”
Section: Children With Rsv Experience a Loss Of Quality Of Life Due T...mentioning
confidence: 99%